Fast High‐Responsivity Few‐Layer MoTe2 Photodetectors. Issue 11 (16th August 2016) - Octon, Tobias J.; Nagareddy, V. Karthik; Russo, Saverio; Craciun, Monica F.; Wright, C. David
Abstract : The transition metal dichalcogenide MoTe2 is fabricated into few‐layer field‐effect transistors that show hole conduction with a mobility of 2.04 V cm −2 s −1 . Four‐layer MoTe2 devices have a high photoresponsivity of 6 A W −1 and a response time, at around 160 μs, over 100 times faster than previously reported, making them a strong candidate for high speed and high sensitivity photodetection.